“This England”: Re-Visiting Shakespearean Landscapes and Mediascapes in John Akomfrah’s The Nine Muses (2010) - Calbi, Maurizio (Multicultural Shakespeare: Translation, Appropriation and Performance, 2017)
The paper will offer a reading of John Akomfrah’s The Nine Muses (2010), a 90-minute experimental feature film that has been defined as “one of the most vital and original artistic responses to the subject of immigration that British cinema has ever produced” (Mitchell). It will focus on the multifarious ways in which the film makes the “canonical” literary material that it incorporates, including Shakespeare, interact with rarely seen archival material from the BBC regarding the experience of Caribbean and South Asian immigrants in 1950s and 1960s Britain. It will argue that through this interaction the familiarity of Western “canonical” literature re-presents itself as an uncanny landscape haunted by other stories, as a language that is already in itself the “language of the other” (Derrida). In particular, it will claim that Shakespearean fragments are often used in an idiosyncratic way, and they repeatedly resonate with some of the most fundamental ethical and political issues of the film, such as the question of England as “home” and migration. The paper will also argue that the decontextualization and recontextualization of these fragments makes them re-emerge as part of an interrogation of the mediality of the medium, an interrogation that also offers insights into the circulation of Shakespeare in the contemporary mediascape.